SISTEM INFORMASI PENGOLAHAN DATA NILAI SISWA: (Studi Kasus: SMK Taruna Bangsa Ciamis) - Abdurrahman; Siti Solihah (LPPM STMIK Bandung, 2021)
SMK Taruna Bangsa is a private school that has several departments, namely: Network Communication Engineering, Light Vehicle Engineering, Motorcycle Engineering, Nursing, Pharmacy, and Office Automation and Governance. The Web-based Student Value Data Processing Information System is a system that provides information on student activeness reports online, in the form of report values and student-related information, based on the web. This system helps improve the speed and quality of delivering information. The problems identified in this study include frequent delays in informing students of their grades, delays in tracking student progress each year, and difficulties in printing exam cards quickly. To address these issues and meet the objectives of the study, it is necessary to apply the PIECES analysis method. The aim of this study is to accelerate the process of providing academic information to students, teachers, and parents. The Student Value Data Processing Information System is an academic service designed for students, teachers, and parents at SMK Taruna Bangsa to access information related to academic records throughout the learning process. The information delivered includes student data, teacher data, grade data, attendance, and exam card printing.